Bahasa Inggris - Devi Permatasari; Niya Fajar Wati; Chori Elsera; Puput Risti Kusumaningrum; Sri Sat Titi Hamranani (KHD Production, 2025)
Menstrual hygiene management is an action to maintain cleanliness and health when women experience menstruation. If not appropriately implemented, young women will not be able to meet their needs for cleanliness, appearance, and reproductive health during pregnancy. So, it is easier to get urinary tract infections, vaginal discharge, cervical cancer, and other reproductive health problems. This study aimed to determine what factors influence menstrual hygiene management. This study used a sample of 103 adolescents in the Klaten area. This research was conducted using a cross-sectional method using a total sampling technique. The menstrual hygiene management questionnaire has been tested for validity and reliability with a value of r = 0.69. after being tested using Kendall's Tau test, the results showed that menarche's age (0.077 > 0.05) did not correlate with menstrual hygiene management. Cycle menstruation (0.025 < 0.05) influences menstrual hygiene management. Knowledge (0.043 < 0.05) influences menstrual hygiene management. Attitude (0.592 > 0.05) does not influence menstrual hygiene management. Myth or trust (0.049 < 0.05) influences menstrual hygiene management. The most influential factor in menstrual hygiene management is cycle menstruation.